Forests and the Forest Resources of the U.S.S.R. - Nair, P. N. (Indian Forester, 1966)
About one fourth of the forests in the world belongs to the U.S.S.R. The wooded forest area in the Soviet Union comes to about 33.2 per cent of the country's total area. There are different forest types with many sub-divisions differing in their geographical distribution, composition and productivity. Most of the forest wealth in the country is mainly concentrated in the north temperate zone. The predominant species are spruce, fir, pines, larch, birch, aspen, oaks, chestnut, etc., and each genus is represented by many species and forms. Natural regeneration of these forests is satisfactory. The forests in the U.S.S.R. are very important natural resources and they playa very important role in the national welfare. The resourCes of timber in this country comprises about 80 billion cu m. Considerable portions of these forests have not yet been tapped. Attempts are afoot in increasing the productivity of the forests particularly the low productive forests by artificial and natural regeneration m ethods. About 2.5 million hectares are thus being regenerated annually in recent years, of which about 1.2 million hectares are tackled by artificial means. The magnitude of various forestry operations is so huge that a variety of mechanical device, have been developed to ensure their speedy excution. The world wide accepted theme of multiple use of forests is the main aim of Soviet forestry also. A variety of products are being manufactured out of the forest produces . One of the increasing use of forest timber is for the production of pulp and paper. Spruce and fir arc mainly used in this industry. A beginning has been made in the use of broadleaved species also in this industry. A brief outline on the forests and forest resources in U.S.S.R. is the aim of this article.